2017
DOI: 10.1681/asn.2016050573
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-to-Myofibroblast Transition Contributes to Interstitial Fibrosis in Chronic Renal Allograft Injury

Abstract: Interstitial fibrosis is an important contributor to graft loss in chronic renal allograft injury. Inflammatory macrophages are associated with fibrosis in renal allografts, but how these cells contribute to this damaging response is not clearly understood. Here, we investigated the role of macrophage-to-myofibroblast transition in interstitial fibrosis in human and experimental chronic renal allograft injury. In biopsy specimens from patients with active chronic allograft rejection, we identified cells underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
219
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(258 citation statements)
references
References 51 publications
14
219
0
Order By: Relevance
“…Mechanistically, M2 cells can produce growth factors such as TGF-β and PDGF, which are crucial mediators of vascular changes by inducing smooth muscle cell proliferation, activation of myofibroblasts and extracellular matrix deposition (32, 33). Moreover, a recent report indicates that α-SMA + myofibroblasts contributes to interstitial fibrosis in chronic renal allograft injury, and approximately 50% of these myofibroblasts are derived from M2 macrophages (34). All these studies suggest the significance of M2 macrophages in mediating chronic allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, M2 cells can produce growth factors such as TGF-β and PDGF, which are crucial mediators of vascular changes by inducing smooth muscle cell proliferation, activation of myofibroblasts and extracellular matrix deposition (32, 33). Moreover, a recent report indicates that α-SMA + myofibroblasts contributes to interstitial fibrosis in chronic renal allograft injury, and approximately 50% of these myofibroblasts are derived from M2 macrophages (34). All these studies suggest the significance of M2 macrophages in mediating chronic allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Moreover, a recent report indicates that α-smooth muscle actin positive myofibroblasts contribute to interstitial fibrosis in chronic renal allograft injury, and that approximately 50% of these myofibroblasts are derived from M2 macrophages. 34 All these studies suggest the significance of M2 macrophages in mediating chronic allograft rejection. In the present study we found that mTOR deletion in macrophages inhibited M2 polarization in vitro, thereby decreased the expression of M2 marker genes in graft-infiltrating macrophages, and prevented the development of transplant vasculopathy following CTLA4-Ig treatment.…”
Section: Data From Clinical and Preclinical Studies Repeatedly Demonsmentioning
confidence: 97%
“…6 This finding is in keeping with a possible role of macrophages in promoting the activation and recruitment of myofibroblasts to areas of inflammation and eventually leading to fibrosis 11 and is consistent with a recent paper reporting that the macrophage-to-myofibroblast transition may contribute to interstitial fibrosis in both human and experimental chronic allograft injury. 12 Moreover, macrophage infiltration is also associated with poor long-term eGFR behavior in kidneys from deceased but not from living donors, thus confirming a potential role of early inflammation in the risk of subsequent CKD in KTRs after transplantation, and somewhat explaining the better outcome observed in KTRs receiving kidneys from living donors. 13 Another important finding of our study is that in our patients early and severe macrophage infiltration proved to be even more predictive of subsequent graft loss than early IFTA, which characterizes chronic kidney allograft dysfunction and usually develops before any significant clinical evidence of graft damage appears.…”
Section: Discussionmentioning
confidence: 83%
“…Renal interstitial fibrosis (RIF) is a common pathway leading to the progressive loss of kidney function in CKD [7]. Accumulating studies have illustrated that macrophages play a role in RIF, and we thus speculate that macrophage autophagy can prevent RIF [8][9][10]. Understanding the molecular signaling mechanisms underlying the involvement of macrophage autophagy in RIF will lead to novel treatments of CKD.…”
Section: Introductionmentioning
confidence: 90%